Comprehensibility and liveliness in nonnative student oral presentations before and after training: A mixed methods study. (December 2016) - Lima, Edna F.
Abstract: This mixed methods study analyzes comprehensibility and liveliness in nonnative student oral presentations. The purpose of this study is threefold: to investigate the effectiveness of training nonnative students in prosody and oral presentations skills; to examine the relationship between accentedness and comprehensibility; and to examine whether speakers receive more positive comprehensibility ratings from listeners of the same L1 background as compared to listeners with different L1s. The study involved four Chinese speakers and 64 listeners from 14 different L1 backgrounds. Inferential statistics reveal different levels of improvement for the four speakers. An analysis of the ratings assigned to "accent" and "comprehensibility" shows that even when accent is perceived as strong, it does not hinder comprehensibility. As for the comparison between comprehensibility ratings from Chinese listeners and other L1 background listeners, results from eight independent two-sample t-tests show only two significant instances; in those two instances, the comprehensibility ratings assigned by listeners that share the speakers' L1 (Chinese) were more positive than the ratings assigned by listeners from other L1 backgrounds. The findings yielded in this study indicate that training in prosody and oral presentation skills is effective and may help the academic success of international students.